RcLS2F – A Novel Fungal Class 1 KDAC Co-repressor Complex in Aspergillus nidulans - Bauer, Ingo; Gross, Silke; Merschak, Petra; Kremser, Leopold; Karahoda, Betim; Bayram, Özlem Sarikaya; Abt, Beate; Binder, Ulrike; Gsaller, Fabio; Lindner, Herbert; Bayram, Özgür; Brosch, Gerald; et al. (Frontiers in Microbiology, 2020)
The fungal class 1 lysine deacetylase (KDAC) RpdA is a promising target for prevention and treatment of invasive fungal infection. RpdA is essential for survival of the most common air-borne mold pathogen Aspergillus fumigatus and the model organism Aspergillus nidulans. In A. nidulans, RpdA depletion induced production of previously unknown small bioactive substances. As known from yeasts and mammals, class 1 KDACs act as components of multimeric protein complexes, which previously was indicated also for A. nidulans. Composition of these complexes, however, remained obscure. In this study, we used tandem affinity purification to characterize different RpdA complexes and their composition in A. nidulans. In addition to known class 1 KDAC interactors, we identified a novel RpdA complex, which was termed RcLS2F. It contains ScrC, previously described as suppressor of the transcription factor CrzA, as well as the uncharacterized protein FscA. We show that recruitment of FscA depends on ScrC and we provide clear evidence that ∆crzA suppression by ScrC depletion is due to a lack of transcriptional repression caused by loss of the novel RcLS2F complex. Moreover, RcLS2F is essential for sexual development and engaged in an autoregulatory feed-back loop.